When Students Say Far Too Much: Examining Gushing in the ELT Classroom - Mugford, Gerrard; Ramírez Cuevas, Oscar (Profile: Issues in Teachers’ Professional Development, 2015)
English foreign-language users often overuse words when faced with difficult situations. Called gushing, such excessive use of words is often legitimately employed by native speakers to express, for instance, gratitude and apologies when a simple thank you or sorry does not sufficiently convey an interlocutor’s feelings. This paper examines the appropriateness and effectiveness of gushing when employed by advanced students facing difficult situations. Answering discourse completion tasks, students from a private university in Guadalajara, Mexico were asked to employ acquiescing, persisting, and aggressing strategies to resolve two particular situations. The results indicate that gushing was widely used, but in communicatively ineffective ways, reflecting an area where teachers can help develop students’ communicative competencies. Los hablantes del inglés como lengua extranjera frecuentemente usan palabras en exceso cuando enfrentan situaciones difíciles. Hablantes nativos utilizan un excesivo número de palabras para expresar, por ejemplo, gratitud y disculpas cuando un simple gracias o lo siento no transmite completamente los sentimientos del interlocutor. Este artículo examina el uso excesivo de palabras por alumnos con un nivel avanzado de inglés al enfrentarse a situaciones difíciles. Al responder un cuestionario de completación, alumnos universitarios en Guadalajara, México, usaron estrategias conciliadoras, interrogatorias y argumentativas para resolver dos situaciones específicas. Los resultados indican que un uso excesivo de palabras fue utilizado pero en formas comunicativamente ineficaces y reflejan un área donde los profesores pueden ayudar a los alumnos a desarrollar competencias comunicativas.